The Future of Diagnosis: What is Automated Machine Learning (AutoML) in Healthcare? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Introduction: The AI Revolution in Clinical Practice The integration of Artificial Intelligence (AI) into healthcare is rapidly transforming clinical pr...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation